2018
DOI: 10.1097/md.0000000000012970
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and outcome of acute gastrointestinal injury in critically ill patients

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 22 publications
(31 reference statements)
2
30
4
1
Order By: Relevance
“…These children were signi cantly more severely ill (lower GCS scores and higher SOFA scores and PCISs) and exhibited greater morality than those without FI. The prevalence of FI was lower than that in previous studies on adult critically ill patients [17,18]. The reasons for this result are not clear.…”
Section: Discussioncontrasting
confidence: 82%
“…These children were signi cantly more severely ill (lower GCS scores and higher SOFA scores and PCISs) and exhibited greater morality than those without FI. The prevalence of FI was lower than that in previous studies on adult critically ill patients [17,18]. The reasons for this result are not clear.…”
Section: Discussioncontrasting
confidence: 82%
“…However, few studies on gastrointestinal injury have been reported in patients with COVID-19. Gastrointestinal dysfunction is common and closely related to adverse outcomes in critically ill patients[ 10 , 15 - 17 ]. In 2012, the Working Group on Abdominal Problems of the European Society of Intensive Care Medicine developed the definitions and a grading system for AGI in intensive care patients[ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…AGI was also correlated with clinical severity and outcomes of this novel disease. A recent meta-analysis showed that the incidence of AGI was about 40% and mortality was 33% in critically ill patients[ 15 ]. The corresponding data in this study were higher than those in previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Відомо, що наявність порушення функції ШКТ в структурі коморбідних станів погіршує клінічний перебіг захворювання і прогноз пацієнта [25,26]. Зважаючи на це, вищенаведені зміни є обґрунтованою підставою для покращення клінічного перебігу захворювання, що проявляється в зменшенні тяжкості стану новонароджених за шкалою NTISS і підвищенні їх виживаності.…”
Section: рисунок 1 частота позитивної клінічної динаміки сгін в групunclassified